1967
DOI: 10.1002/pol.1967.150050831
|View full text |Cite
|
Sign up to set email alerts
|

Influence of intrachain interactions on the kinetics of styrene polymerization and copolymerization

Abstract: SynopsisIn the free-radical polymerization of styrene, it has been observed that the onset of an acceleration of the polymerization due to increased solution viscosity can be quantitatively measured as occurring at a critical point. The product of the degree of polymerization of the polymer in solution at the critical point times its volume fraction can be represented by a temperature-dependent constant (P,V, = K ) . The value of the constant passes through a maximum between 60 and 90°C. The value of the const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

1970
1970
1985
1985

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 13 publications
1
24
0
Order By: Relevance
“…In the case of copolymers and other complex polymers, the spectra (E,,,) which correspond to some of the species present can be obtained directly from the homopolymers of the monomers used to synthesize the polymer. If there are no effects on the absorption behaviour due to inter-and intramolecular interactions between the functionalities present in the solvent and in the polymer molecule, the direct application of [2] or [3] together with the spectra of the homopolymers and the initiator fragments should yield the copolymer composition estimates. However, if interactions are present, as in the case of styrene copolymerized with polar comonomers (4), the spectra of the chromophores present may be altered in an, as yet unknown, fashion.…”
Section: Methods Of Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…In the case of copolymers and other complex polymers, the spectra (E,,,) which correspond to some of the species present can be obtained directly from the homopolymers of the monomers used to synthesize the polymer. If there are no effects on the absorption behaviour due to inter-and intramolecular interactions between the functionalities present in the solvent and in the polymer molecule, the direct application of [2] or [3] together with the spectra of the homopolymers and the initiator fragments should yield the copolymer composition estimates. However, if interactions are present, as in the case of styrene copolymerized with polar comonomers (4), the spectra of the chromophores present may be altered in an, as yet unknown, fashion.…”
Section: Methods Of Analysismentioning
confidence: 99%
“…These deviations have been attributed to the microstructure of the polymer chains (3,4,8,10, I I) and in some cases to the conformation of the molecules in solution (2, 6, 9). Vala and Rice (2) observed that the extinction coefficient of isotactic polystyrene at certain wavelengths is smaller than the corresponding extinction coefficients for atactic polystyrene.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations